Mathematics of finance - Cissell, Helen; Cissell, Robert; Flaspohler, David C. (Boston : Houghton Mifflin, 1990)
This book is about: Simple interest; Bank discount; Compound interest; Ordinary annuities; Amortization and Sinking funds; ...
Keywords: Business mathematics; Business mathematics